Analisis Penerapan Sistem Informasi Akuntansi di Koperasi Pegawai Negeri Dewantara SMA Negeri 6 Kota Bengkulu - Vika Fitranita; Della Orseta (Departement of Mathematics Education, 2023)
This study aims to analyze and describe the application of accounting information systems at KPN Dewantara. This study used a qualitative approach with a descriptive research design. Primary data collection was carried out by in-depth interviews with 5 informants who were members, administrators and supervisors of KPN Dewantara. The results showed that the implementation of the accounting information system in the form of microsoft excel at KPN Dewantara was considered good, the selection of microsoft excel based on the needs of KPN Dewantara management, effectiveness was assessed as good by fulfilling 5 indicators of effectiveness, although in the near future microsoft excel will soon be replaced with a new system called cooperative. 4.0. However, the quality of financial reports can only be assessed as good from an internal KPN Dewantara perspective because KPN is not yet guided by PSAK and only uses SAK-ETAP as a guideline for preparing financial reports. The limitations of this study are that there is still a lack of data collection, and the subjects used have not used PSAK as a guideline for making financial reports so that this research has not been able to fully describe the real conditions and conditions of cooperatives in the city of Bengkulu.